Detcetion Of Bacterial Contamination Of Drinking Water In The Right Side Of Mosul City By Multiple Tubes Fermentation Technique. - Adeba AL-Nuaaman; Musaab Al- Ballo (College of Education for Pure Sciences, 2019)
This study aimed to investigate bacterial contamination of drinking water in the right side of Mosul city using multiple tubes fermentation technique, depending on total coliform count as an indicator, this study takes seven months started from December, 2017 to June, 2018.      Three hundered fifteen smples were collected from water purification plants and 12 quarters in the right side of Mosul city include (Msherfa, 17-Tamoz, Al-refaee, Tal- alromman, Al-moa'alemen, Al-shohada'a, Nabls, Al-resala, Al-a'amel, Al-tayaran, Wadi hajar and Al-mansour).     The results showed contaminate of water in purification plants during April and May only while  the contamination wase in all study months of the water reaching consumers with a rate reaching 40.5% of total samples and the highest was in Al-refaee quarter (71.4%) whereas the lowest reached 14.3% in Nabls quarter, the results also showed variations in the contamination during the study monthes, it's highest in May as it reached 83.3% whereas the lowest was in January as it reached 16.7%. The results of chlorine concentration test showed that  the residual chlorine was less than the accepted levels in some quarters formed a ratio reached 32.1%, while it was higher than the accepted level at a ratio of 2.4%, whereas the residual chlorine in 65.5% from total samples was within the accepted level. In this study we isolate and identificate some of the contaminating bacteria such as Escherichia coli , Klebsiella  pneumoniae,  Enterobacter  cloacae, Enterobacter  aerogenes , Proteus mirabilis, Citrobacter  freundii and Salmonella  typhi , Escherichia coli forming the higher rate 40.8% whereas the lower was Citrobacter  freundii 4.1%  . Pseudomonas aeruginosa was also isolated in this study at 14.3% of the total isolated bacteria.